After RIPCORD 2, FAME 3, FLOWER-MI and FUTURE: Has the Pressure Wire had its Day? - Bhavik Modi; Subhabrata Dutta; Damien Collison; Ioannis Lampadakis; Sayan Sen (Interventional Cardiology: Reviews, Research, Resources)
Recent years have seen the publication of several high-profile, negative trials about pressure wires. This has coincided with a consistent increase in the ratio of angioplasty for acute coronary syndromes versus percutaneous coronary intervention in stable coronary artery disease, a greater use of intracoronary imaging during percutaneous coronary intervention and the continued evolution of computational fluid dynamics-derived estimations of fractional flow reserve from both CT and invasive coronary angiography. Consequently, many interventional cardiologists now wonder if the pressure wire will soon become obsolete. This head-to-head article provides a critical appraisal of recent trial data, discusses a potential evolution in how pressure wires are used and debates the motion that the device (and by extension, invasive assessment of coronary physiology) has now had its day.